The influence of motivation and work environment with leadership style as intervening to performance of employees in the Secretariat of DPRD, Pariaman City - Afni Idra, Zul; Heryanto, (Technium Social Sciences Journal, 2020)
This study aims to determine the effect of motivation and work environment on leadership style and its impact on employee performance at the Pariaman City DPRD Secretariat. This research is motivated by the low work motivation of employees and the conditions of the work environment that do not support employees in carrying out work and leadership style that does not support employees in carrying out work, thus affecting the decline in employee performance at the Pariaman City DPRD Secretariat. The research method with a quantitative approach with the path analysis method. Data collection techniques with questionnaires, observation and interviews. The respondents of this study were 50 employees of the Pariaman City DPRD Secretariat. The sampling method uses the total sampling method in which the entire population in this study is the research sample. Hypothesis testing is calculated by the Statistical Package for Social Science (SPSS) program version 20.0. The results of this study found that motivation does not significantly influence leadership style, work environment does not significantly influence leadership style, motivation has significant effect on performance, work environment has a significant effect on performance, and leadership style has a significant effect on employee performance at the Pariaman City DPRD Secretariat. Whereas directly motivation through leadership style has a significant influence on performance and indirectly the work environment through leadership style has a significant influence on the performance of the Pariaman City DPRD Secretariat staff. Keywords: Motivation, Work Environment, Leadership Style, Employee Performance